2010
DOI: 10.1093/hmg/ddq512
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive shock ameliorates disease processes and extends survival in huntingtin mutant mice

Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder caused by expanded polyglutamine repeats in the huntingtin (Htt) protein. Mutant Htt may damage and kill striatal neurons by a mechanism involving reduced production of brain-derived neurotrophic factor (BDNF) and increased oxidative and metabolic stress. Because electroconvulsive shock (ECS) can stimulate the production of BDNF and protect neurons against stress, we determined whether ECS treatment would modify the disease process and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 78 publications
2
10
0
Order By: Relevance
“…Recently, Mughal et al demonstrated that ECT could protect neurons against mutant huntingtin protein resulting in improved functional outcome, leading to slow disease progression [9]. In agreement with Mughal et al, the results of brain MRI and MMSE scores of before and after treatment, showed that the cognitive function of our patient remained clinically unchanged.…”
supporting
confidence: 88%
“…Recently, Mughal et al demonstrated that ECT could protect neurons against mutant huntingtin protein resulting in improved functional outcome, leading to slow disease progression [9]. In agreement with Mughal et al, the results of brain MRI and MMSE scores of before and after treatment, showed that the cognitive function of our patient remained clinically unchanged.…”
supporting
confidence: 88%
“…Previous studies have indicated that the level of BDNF was reduced in many neurodegenerative diseases, such as Huntington's disease (26), multiple sclerosis (27), and Parkinson's disease (28). In this research, we found that BDNF is also significantly decreased in the body fluid of patients and an animal model.…”
Section: Discussionsupporting
confidence: 53%
“…BDNF stimulates and controls growth of new neurons from neural stem cells (neurogenesis) [ 5 , 6 ], and BDNF protein and mRNA have been identified in most brain areas including the olfactory bulb, cortex, hippocampus, basal forebrain, mesencephalon, hypothalamus, brainstem and spinal cord. The levels of BDNF are decreased in many neurodegenerative diseases such as Parkinson's disease (PD) [ 7 ], multiple sclerosis (MS) [ 8 ] and Huntington's disease [ 9 ]. Besides the neuroprotective effect, BDNF plays a major role in energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%